A. First you must start by plugging in your equation solve Y = 2(5) + 1 then you must simplify by solving your 2×5+ 1 and then you end up with Y equals 11
B. Again plug in your equation Y = 2(-5) + 1 then you must simplify by solving your 2×-5+ 1 and then you end up with Y equals -10+ one which simplifies to y = -9
I hope this helps
Answer:
Step-by-step explanation:
By proportion it will be (5/3) * 12
= 60/3
= 20 days.
Answer:
5![\sqrt{5}](https://tex.z-dn.net/?f=%5Csqrt%7B5%7D)
Step-by-step explanation:
Using the rule of radicals
×
⇔
, then
![\sqrt{125}](https://tex.z-dn.net/?f=%5Csqrt%7B125%7D)
= ![\sqrt{25(5)}](https://tex.z-dn.net/?f=%5Csqrt%7B25%285%29%7D)
=
× ![\sqrt{5}](https://tex.z-dn.net/?f=%5Csqrt%7B5%7D)
= 5![\sqrt{5}](https://tex.z-dn.net/?f=%5Csqrt%7B5%7D)
Answer:
Step-by-step explanation:
k=3 or k=−7 both choices are correct
Answer:
Inverse of
![\frac{x + 4}{5}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%20%2B%204%7D%7B5%7D)
Step-by-step explanation:
Let y = -5x-4
Swap y and x
x = -5y -4
Solve for y
x+4 = -5y
which is the inverse